2016
DOI: 10.1172/jci86905
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming metabolism by targeting sirtuin 6 attenuates retinal degeneration

Abstract: Retinitis pigmentosa (RP) encompasses a diverse group of Mendelian disorders leading to progressive degeneration of rods and then cones. For reasons that remain unclear, diseased RP photoreceptors begin to deteriorate, eventually leading to cell death and, consequently, loss of vision. Here, we have hypothesized that RP associated with mutations in phosphodiesterase-6 (PDE6) provokes a metabolic aberration in rod cells that promotes the pathological consequences of elevated cGMP and Ca 2+, which are induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
119
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(124 citation statements)
references
References 89 publications
5
119
0
Order By: Relevance
“…For example, retinal genetic rescue at advanced disease stages does not lead to OS regeneration (5,18,19), suggesting a correlation between photoreceptor numbers and OS synthesis. Perhaps a critical number of rods might be needed to release glucose from RPE, where it is sequestered following rod degeneration and thus unavailable to support OS synthesis (8,20). Interestingly, in untreated RP patients (and mice), the earliest detected histopathologic change is rod OS dysgenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, retinal genetic rescue at advanced disease stages does not lead to OS regeneration (5,18,19), suggesting a correlation between photoreceptor numbers and OS synthesis. Perhaps a critical number of rods might be needed to release glucose from RPE, where it is sequestered following rod degeneration and thus unavailable to support OS synthesis (8,20). Interestingly, in untreated RP patients (and mice), the earliest detected histopathologic change is rod OS dysgenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A potential therapeutic approach for RP is to reprogram metabolic pathways that are altered during rod dystrophy and RP progression. In one such approach, we found that knocking down sirtuin-6 (SIRT6) to reprogram retinal cells toward anabolism delayed photoreceptor cell degeneration in a mouse model of RP [24]. For this study, we applied a liquid biopsy proteomics approach to identify the molecular pathway targets affected during RP progression.…”
Section: Introductionmentioning
confidence: 99%
“…Cone photoreceptors are indispensable for human vision in daylight and their loss in inherited or acquired retinal diseases have devastating effects on daily tasks and life quality (27,45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant HDAC activity is causatively linked to various diseases ranging from cancer, through muscular dystrophies, to neurodegenerative diseases (22,23). We and others have previously shown that regulation of epigenetic patterns, via HDAC inhibition can protect primary degenerating photoreceptors in inherited retinal dystrophies caused by mutations in different genes (24)(25)(26)(27)(28). Consequently, more than 90 clinical trials involving HDAC regulators stress HDAC inhibition as promising therapeutic approach for various diseases including retinal dystrophies (21,29).…”
Section: Introductionmentioning
confidence: 99%